Prevalencia de enfermedad periodontal en América del sur en adultos de 20 a 60 años de edad, revisión de la literatura (2020)
The periodontal disease is a chronic inflammatory disease of the periodontium and its advanced stage is characterized by the loss of the periodontal ligament and the destruction of the surrounding alveolar bone. Objective: To determine the prevalence of periodontal disease in South America in adults 20-60 years of age, according to a literature review. Materials and Methods: A search was made for indexed articles related to the prevalence of periodontal disease and associated risk factors in 8 biomedical platforms such as Pubmed, Science Direct, Springer Link, SciElo, academic Google, ELSEVIER, University database Antonio Nariño, and database of the Pontificia Universidad Javeriana, 48 articles related to the topics were obtained, of which 17 reported prevalences of periodontal disease in South America, and associated risk factors in periodontal disease, published between 2006 and 2019.